Hacking the Academy: New Approaches to Scholarship and Teaching from Digital Humanities - Cohen, Daniel J.; Scheinfeldt, Tom (Digital Humanities, 2013)
"On May 21, 2010, Daniel J. Cohen and Tom Scheinfeldt posted the following provocative questions online: "Can an algorithm edit a journal? Can a library exist without books? Can students build and manage their own learning management platforms? Can a conference be held without a program? Can Twitter replace a scholarly society?" As recently as the mid-2000s, questions like these would have been unthinkable. But today serious scholars are asking whether the institutions of the academy as they have existed for decades, even centuries, aren't becoming obsolete. Every aspect of scholarly infrastructure is being questioned, and even more importantly, being hacked. Sympathetic scholars of traditionally disparate disciplines are canceling their association memberships and building their own networks on Facebook and Twitter. Journals are being compiled automatically from self-published blog posts. Newly minted PhDs are forgoing the tenure track for alternative academic careers that blur the lines between research, teaching, and service. Graduate students are looking beyond the categories of the traditional CV and building expansive professional identities and popular followings through social media. Educational technologists are "punking" established technology vendors by rolling out their own open source infrastructure. Here, in Hacking the Academy, Daniel J. Cohen and Tom Scheinfeldt have gathered a sampling of the answers to their initial questions from scores of engaged academics who care deeply about higher education. These are the responses from a wide array of scholars, presenting their thoughts and approaches with a vibrant intensity, as they explore and contribute to ongoing efforts to rebuild scholarly infrastructure for a new millennium."